Primary health care: nutritional and functional profile of elderly people - de Sousa Machado, Jacqueline; de Souza, Vanessa Vicente; de Oliveira Silva, Shirlei; Abdala Frank, Andréa; Abreu Soares, Eliane (O Mundo da Saúde, 2007)
The AIM of this study was to establish the nutritional and functional profile of elderly people treated in the nutrition ward of José Paranhos Fontenelle Clinic (Rio de Janeiro - Brazil) for their first medical care. The research involved the participation of 35 people. It was based on anthropometric assessment and collected data on socio-economic, biochemical and dietary factors. It also included an investigation about their daily life activities to evaluate the results of care. Taking into account socio-economical aspects, the study shows that 44.4% of men and 57.7% of women have an income less than two Brazilian minimum wages. Concerning the anthropometric assessment it was observed a high prevalence of obesity for both sexes, besides a high risk of cardiovascular diseases. Arterial hypertension was the most frequent disease among males (55.5%), and dyslipidemia among females (88.4%). In relation to Daily Life Activities (DLA`s), the ones they showed more difficulties to perform were climbing stairs (40%), taking a bus (25.7%) and trimming toes nails (23.07%). In relation to dietary intake, a high amount of rice, bread and beans consumption was detected. The most frequently consumed protein source was chicken meat. Despite this, a low consumption of fruits and vegetables persists that justifies an adequate nutritional orientation.